2007
DOI: 10.1016/j.tca.2006.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic non-equilibrium thermodynamics in dynamic calorimetry

Abstract: What is really measured in dynamic calorimetric experiments is still an open question. This

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 94 publications
(166 reference statements)
0
64
0
Order By: Relevance
“…This general expression has been used by one of us to derive the so-called expression of the frequency dependent complex heat capacity under linear regime assumption. 33 Following the same principle, Schmelzer and coworkers 18,24 have derived these results basing their reasoning solely on the order parameter ξ . In extending their result to the affinity they conclude that the derivative of the affinity can be neglected in the Eq.…”
Section: Configurational Specific Heatmentioning
confidence: 98%
“…This general expression has been used by one of us to derive the so-called expression of the frequency dependent complex heat capacity under linear regime assumption. 33 Following the same principle, Schmelzer and coworkers 18,24 have derived these results basing their reasoning solely on the order parameter ξ . In extending their result to the affinity they conclude that the derivative of the affinity can be neglected in the Eq.…”
Section: Configurational Specific Heatmentioning
confidence: 98%
“…It is expected that dynamic calorimetry can provide an insight into the energy landscape dynamics; cf., for example, [89][90][91][92]. Usually, one associates the imaginary part of linear susceptibility with the absorption of energy by the sample from the applied field.…”
Section: Complex Heat Capacitymentioning
confidence: 99%
“…For more detailed discussions and studies the reader is referred to Birge and Nagel (1985), Garden (2007aGarden ( , 2007b or Lion and Yagimli (2009). In Lion and Yagimli (2009), it has been shown that the imaginary part of the complex specific heat (4.12) can be attributed to the entropy production per temperature cycle.…”
Section: Frequency-dependence Of Specific Heat and Thermal Expansionmentioning
confidence: 99%